THE EFFECTIVENESS OF GAMIFIED LEARNING ENVIRONMENTS IN IMPROVING LITERACY SKILLS AMONG PRIMARY SCHOOL STUDENTS - Sarah Nasution; Sri Handayani Hsb; Anita Adinda (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effectiveness of gamified learning environments in improving literacy skills among primary school students. Gamification, which incorporates game elements such as points, badges, levels, and challenges into the learning process, is considered capable of enhancing motivation and student engagement—particularly in literacy learning, which young learners often perceive as less appealing. This research employed a mixed-methods design involving students from both lower and upper primary grades as research subjects. Quantitative data were collected through literacy tests and motivation questionnaires, while qualitative data were gathered through observations and interviews. The findings reveal that gamified learning environments significantly improve students’ reading comprehension, vocabulary mastery, and reading interest. Moreover, game elements such as challenges and rewards positively influence students’ learning motivation and persistence in completing literacy tasks. These results highlight gamification as an effective and innovative approach to enhancing literacy skills, making it a valuable strategy for integration into primary school instruction.